PRINSIP HAKIM AKTIF DALAM PERKARA PERDATA - Sunarto, Sunarto (Jurnal Hukum dan Peradilan, 2016)
The Justice must be firmly maintained. This demand can not be modified due to it was closely related to the rights enforcement. The common paradigm in civil code perception makes judges passively work in civil cases handling. It can be seen in Article 119 HIR when the general court chief judge give a support as advice and help related to the formality or the terms of the lawsuit for the strike to be acceptable and meets the requirements of formality lawsuit against the plaintiff or attorney. Moreover , Article 130 HIR/RBG Article 154, required that general court chief judge attempted to reconcile the two parties litigant. Furthermore, in Article 132 HIR/RBG Article 156, the Judge has an active role to inform both litigants and provide an explanation to the litigants of their rights to take legal actions and the right to submit evidence on the court.Keywords : active judges, civil case